Community-Based Interventions in Prepared-Food Sources: A Systematic Review - Gittelsohn, Joel (Centers for Disease Control and Prevention, 2013)
INTRODUCTION: Food purchased from prepared-food sources has become a major part of the American diet and is linked to increased rates of chronic disease. Many interventions targeting prepared-food sources have been initiated with the goal of promoting healthful options. The objective of this study was to provide a systematic review of interventions in prepared-food sources in community settings. METHODS: We used PubMed and Google Scholar and identified 13 interventions that met these criteria: 1) focused on prepared-food sources in public community settings, 2) used an impact evaluation, 3) had written documentation, and 4) took place after 1990. We conducted interviews with intervention staff to obtain additional information. Reviewers extracted and reported data in table format to ensure comparability. RESULTS: Interventions mostly targeted an urban population, predominantly white, in a range of income levels. The most common framework used was social marketing theory. Most interventions used a nonexperimental design. All made use of signage and menu labeling to promote healthful food options. Several promoted more healthful cooking methods; only one introduced new healthful menu options. Levels of feasibility and sustainability were high; sales results showed increased purchasing of healthful options. Measures among consumers were limited but in many cases showed improved awareness and frequency of purchase of promoted foods. CONCLUSION: Interventions in prepared-food sources show initial promising results at the store level. Future studies should focus on improved study designs, expanding intervention strategies beyond signage and assessing impact among consumers.